THE USE OF SATELLITE TECHNOLOGY IN PROSPECTING RAILWAYS - Borisov, E. O. (Science and Transport Progress, 2003)
The usage of geodesic satellite apparatus of finding the position for research of railroad is considered in the article. The calculations confirm the accordance to accuracy discrete satellite research to the normative demands. The article has the reviewing character.